The Effect of Sodium Fluoride Administration on IL-1β and TNF-α Expression on Orthodontic Teeth Movement - Rina Sutjiati; Erna Sulistyani; Leliana Sandra Deviade Putri; Rudy Joelijanto; Herniyati Herniyati; Dwi Prijatmoko; Adik Wulandari; Dani Agam Rahmadianto (Health Notions, 2022)
Relapse in post orthodontic treatment is common in the community because resorption in the pressure side occurs excessively due to teeth being moved with an orthodontic device. Excessive resorption can be inhibited by using NaF which has been shown to inhibit osteoclast activity, thereby reducing osteoclast numbers. The purpose of this study was to analyze the effect of NaF administration on IL-1β and TNF-α expression of osteoclast in orthodontic teeth movement. The research used experimental-quantitative research type applying Randomized Posttest Only Control Group Design, by selecting the experimental group and the control group randomly. Animal model using 16 male Wistar rats given orthodontic force using NiTi closed coil spring adjusted to give 10 grams/cm2 of mechanical strength, were applied to the palatal in the maxillary incisors of the Wistar rat teeth. Rats were divided into two groups, the control group (C group) and treatment group (T group) given topical NaF application (11.75 ppm). Immunohistochemical examination was performed to calculate IL-1β and TNF-α expression on osteoclasts on the 7th day and 14th day. The administration of NaF reduces IL-1β and TNF-α osteoclast’s expression both on the 7th day (p <0.05) and 14th day (p <0.05). Data were tested by the Kolmogorov-Smirnov test, Levene test and the difference tested Annova followed by LSD (p <0.05). Topical administration of NaF application to the gingival sulcus of male Wistar rats in orthodontic tooth movement can reduce the number of osteoclasts that express IL-1β in the alveolar bone in the pressure area. Topical administration of NaF application to the gingival sulcus of male Wistar rats in orthodontic tooth movement can reduce the number of osteoclasts that express TNF-α in the alveolar bone in the pressure region. Decreased number of osteoclasts expressing IL-1β and TNF-α significantly occurred on the 7th day and 14th day. Keywords: IL-1β; TNF-α; NaF; osteoclast; orthodontic teeth movement